Efficacy Of Ayurveda Treatment Protocol In The Management Of Ulcerative Colitis W.S.R. To Pravahika - Goran, Arif Khan; Kumar, Mahesh; Mishra, Pramod Kumar; Bhanot, Neha (International Research Journal of Ayurveda & Yoga, 2024)
Ayurveda is a system of medicine with historical roots in the Indian subcontinent. Ayurveda therapies and practices have been integrated in general wellness application and in some cases in medical uses. Ulcerative colitis (UC) is a form of inflammatory bowel disease (IBD) that causes inflammation and ulcers in the colon. The disease is a type of colitis, which is a group of diseases that cause inflammation of the colon, the largest section of the large intestine, either in segments or completely. The main symptom of this active disease is diarrhea mixed with blood. ulcerative colitis (UC) is one with a prevalence rate of 2–3% in the world, The main causes include dietary habits and stress. These habits disturb the internal immunity and develop Auto immune disease in the form of Ulcerative coitis(UC).In Ayurveda,it can be compared with a disease Pravahikacharacterized by Atidrava Mala Pravrutti with Rakta. This topic will be discussed at the